Contact Dermatitis and its Clinical Manifestations: A Case Study - Hadi, Sabaa Hilal (PSM Microbiology, 2025)
With the different seasons of the year, the increasing dust storms in Iraq, and the use of antibacterial soaps, the likelihood of dry skin and the infection with contact dermatitis, a form of skin inflammation that can be either acute or chronic and is brought on by physical or chemical exposure, increase. This paper examines the case of a 32-year-old Iraqi woman who, as a homemaker, frequently used washing products, resulting in severe itching and fluid leakage from lesions in her right hand. A red rash, bumps, blisters, swelling, and dry or itchy skin are all signs of contact dermatitis. Although these rashes are not communicable or fatal, they can cause a great deal of discomfort. Individuals with atopic dermatitis are more vulnerable to bacterial, fungal, and viral infections, most notably, microorganism colonization due to abnormalities in their innate and acquired immune responses. The origins, signs, and therapies for contact dermatitis are illustrated in this instance.